The learning styles of students in the Agricultural Administration program (Journal on studies and research of academic knowledge, 2021)
Talking about the learning style is something as complex as its conceptualization itself, going through the characteristics, traits and existing models. In this research, we worked under the Honney Munfor model of Learning Styles, extended by Alonso et al. (1999), who in turn provided the Honney-Alonso Learning Styles Questionnaire, which is used to determine preferred learning styles. The main object of the research was to analyze the learning styles of students of the career of Administración Agropecuaria of the Facultad de Ciencias Agropecuarias y Forestales Sede San Pedro del Paraná, 2019. A quantitative paradigm was adopted, with a non-experimental cross-sectional design and descriptive level. Bibliographic reviews and field work were carried out, with which it was concluded that students have a high preference for the theoretical style; meanwhile, the predominant characteristics in students are: discoverer, weighted, conscientious, exhaustive, logical, critical, structured, direct, realistic.
Keywords: Learning styles; Preferences; Learning